Esthetic removable partial denture - Tika Rahardjo; Harry Laksono (Indonesian Journal of Prosthodontic, 2023)
Prosthetic rehabilitation of a partially edentulous patient can be established by using wide range of treatment opti-ons. Magnetic attachment retained denture has always been considered beneficial for the patient, because it is gi-ving a more esthetic and functional outlook to the denture. The following case report discusses removable partial denture with no clasps showing by using magnetic attachment retained, thus increase esthetics. A 60-year-old male patient came to Department of Prosthodontics, Airlangga University, for his esthetic problems and chewing inability. Intraoral examination revealed teeth 14, 13, 12, 11, 21, 22, 23, 24, 28, and 46 remained at lower jaw. He never had a denture and needed to make a new one. Clinical and radiographic examination along with the preliminary impress-ion were taken. Teeth preparation and impression for magnet keeper, then cementation of magnet keeper on teeth 12 and 24. Functional impression for upper and lower jaw with individual tray. Denture delivery and one week after followed by insertion of magnet EX 600 in the denture. It was concluded that magnetic attachment retained partial denture could enhance the natural looking for the patient because it has no clasps showing.